PEDAGOGICAL CONDITIONS AND FORMS OF PROFESSIONAL MUSIC TEACHER'S PROFESSIONAL TRAINING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article discusses the pedagogical conditions and forms of improving the professional training of future music teachers through folk songs.